Analisis Penerapan Prespektif Balanced Scorecard terhadap Kinerja UMKM (Studi Empiris Warmindo di Kota Semarang) - Arya Adam Dzulhadi; Puja Wulandari; Nelvana Abdul Aziz; Anisa Windani; Ratih Pratiwi (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2022)
The research was conducted on the MSME commercial sector which aims to find out how much contribution the implementation of the Balanced Scorecard (BSC) has by using four perspectives: finance, customers, internal business processes and learning and growth. The Balanced Scorecard concept is considered in accordance with the consideration that this concept is able to balance short-term plans with long-term plans, as well as balance financial performance with non-financial performance. In addition, the benefit of this research is that the company has the right business strategy and work program that can deal with these changes, enabling it to maintain and expand its business in the future in accordance with its vision and mission. By using this research technique, the application of BSC through four perspectives can make a significant contribution to the company's performance. This shows that MSMEs are continuously oriented towards efforts to maintain customer satisfaction to gain trust from product quality followed by the support of their productive and committed employees who will be able to provide products/services efficiently, consistently and on time by using information technology which has an impact on the ability to organization to generate adequate financial returns